2020 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) 2020
DOI: 10.1109/bibm49941.2020.9313408
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Mixup: Classifying Multi-labeled Medical Images with Corrupted Labels

Abstract: In clinical practice, medical image interpretation often involves multi-labeled classification, since the affected parts of a patient tend to present multiple symptoms or comorbidities. Recently, deep learning based frameworks have attained expertlevel performance on medical image interpretation, which can be attributed partially to large amounts of accurate annotations. However, manually annotating massive amounts of medical images is impractical, while automatic annotation is fast but imprecise (possibly int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…As previous research has demonstrated that CNNs can well process ECG signals [13], [21], we develop an end-to-end CNN to cope with ECG signals for arrhythmia classification.…”
Section: A Automatic Feature Extraction By a Deep Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous research has demonstrated that CNNs can well process ECG signals [13], [21], we develop an end-to-end CNN to cope with ECG signals for arrhythmia classification.…”
Section: A Automatic Feature Extraction By a Deep Neural Networkmentioning
confidence: 99%
“…In early years, various traditional methods employing decision trees [15], SVM [16], random forests [17], and Bayesian networks [18] were applied to classify ECG signals, but did not yield satisfactory performances. Recently, deep learning approaches have drastically improved performances of various recognition tasks, including automatic ECG diagnosis [10], [13], [19]- [22]. Deep learning methods for ECG can be roughly divided into three types, graph based [23]- [25], recurrent neural network (RNN) based [26]- [28], and convolution based [13], [14], [21], [29] methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…. , L}) with L views, we separately deal with these ECG views in parallel by group convolutions, instead of fusing them together as in the previous work [Kachuee et al, 2018;Chen et al, 2020b]. Formally, we predict L basic representations and L groups of deflection representations, and then compute the averaged basic representations Z b and averaged deflection representations Z d over the L views as the input of the decoder.…”
Section: Multi-view Ecg Signal Processingmentioning
confidence: 99%
“…Motivated by representation interpolations [Karras et al, 2019] and Mixup [Zhang et al, 2018;Chen et al, 2020b;Chen et al, 2020a], we synthesize electrocardio field representations of a new ECG by mixing the extracted electrocardio field representations of the same categories (e.g., diseases). As the range of each deflection type varies and the features of different types of deflections should not be mixed for new data synthesis, for this task we train a Nef-Net such that the electrocardio field representation is only predicted by the deflection representation learning branch (i.e., removing the branch for the basic representation).…”
Section: Multi-lead Ecg Synthesis From Scratchmentioning
confidence: 99%